2020
DOI: 10.1016/j.ekir.2020.02.257
|View full text |Cite
|
Sign up to set email alerts
|

Sat-241 Erythrocyte Glutathione Transferase: A Promising Marker for Hemodialysis Adequacy

Abstract: to examine: (1) trends of IDWG among patients in relation to different variables and comorbidities e.g. age, hypertension, diabetes, CV disease...etc.; (2) associations of high IDWG with frequency of hospitalization due to systemic volume overload and the need for extra dialysis sessions, and (3) the impact of high IDWG on the frequency of intradialytic hypotension (IDH). Methods: One hundred and twenty maintenance HD patients were enrolled in this study. All patients had been receiving HD for at least 3 month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 0 publications
2
2
0
Order By: Relevance
“…In our study The post HD analysis of E-GST level showed significant difference between control and conventional HD (p-value 0.001&0.001) respectively This agreed with [7] that showed that the post HD analysis of E-GST level in Post hoc analysis showed significant difference between control and both conventional and HDF patients (P <0.0001, 0.0001) respectively while no significant differences between conventional HD and HDF patients P value (0.061) were observed.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…In our study The post HD analysis of E-GST level showed significant difference between control and conventional HD (p-value 0.001&0.001) respectively This agreed with [7] that showed that the post HD analysis of E-GST level in Post hoc analysis showed significant difference between control and both conventional and HDF patients (P <0.0001, 0.0001) respectively while no significant differences between conventional HD and HDF patients P value (0.061) were observed.…”
Section: Discussionsupporting
confidence: 88%
“…That agreed with (7)who showed that Serum e-GST can predict inadequate dialysis at cut off value>14 ng/ml with area under curve (AUC) 0.871, sensitivity 95%, specificity 60%, PP.V 70.4% and NPV 92.3%. The marker e-Gst was significantly high in patients on conventional HD and HDF (mean _SD 18.35_5.61, 15.20_4.40) respectively compared with control subjects (mean _SD 2.80_1.36) P value <0.0001.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations